2008
DOI: 10.1111/j.1365-2036.2008.03638.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: tranexamic acid for upper gastrointestinal bleeding

Abstract: SUMMARY BackgroundTranexamic acid may reduce upper gastrointestinal bleeding and stabilize patients before endoscopic treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 36 publications
(140 reference statements)
2
29
0
1
Order By: Relevance
“…This molecule prevents fibrin degradation by the plasmin and stabilises the platelet plug by decreasing the converting plasminogen in plasmin, responsible for fibrinolysis during the blood coagulation [8]. Although tranexamic acid is not recommended in the first instance for upper gastrointestinal bleeding, literature attributes it a decrease of mortality without significantly increasing the thromboembolic risk [10].…”
Section: Discussionmentioning
confidence: 99%
“…This molecule prevents fibrin degradation by the plasmin and stabilises the platelet plug by decreasing the converting plasminogen in plasmin, responsible for fibrinolysis during the blood coagulation [8]. Although tranexamic acid is not recommended in the first instance for upper gastrointestinal bleeding, literature attributes it a decrease of mortality without significantly increasing the thromboembolic risk [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the CRASH-2 study, the risk of vaso-occlusive events was not significantly different between TA and placebo as some events occurred in both arms [17]. Safety data on the use of TA were reported in three trials included in a systematic review of TA for upper gastrointestinal bleeding by Gluud et al [16]. Overall, five out of 522 patients (two myocardial infarctions, two pulmonary embolisms and one cerebral infarction) randomized to TA and four out of 526 patients (two myocardial infarctions and two cerebral infarctions) in the placebo group experienced serious thromboembolic events (P = 0.36).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, five out of 522 patients (two myocardial infarctions, two pulmonary embolisms and one cerebral infarction) randomized to TA and four out of 526 patients (two myocardial infarctions and two cerebral infarctions) in the placebo group experienced serious thromboembolic events (P = 0.36). Six patients in the TA group vs. two patients in the placebo group developed deep venous thrombosis (P = 0.96) [16]. In addition, Kakar et al did not observe any deep vein thrombosis in their 50 randomized patients who underwent knee arthroplasty and received either intravenous TA or placebo [19].…”
Section: Discussionmentioning
confidence: 99%
“…31 It has also been shown that the prokinetics (erythromycin or metoclopramide) before endoscopyincrease the visibility during endoscopy 32 and reduces the need for repeat endoscopy, but such practice was not existing. Antifibrinolytics have been found to decrease the mortality rate in patients with non-variceal bleed, 33 but antifibrinolytics were not used in managing any of the patients.…”
Section: Discussionmentioning
confidence: 99%